Peningkatan Hasil Belajar Siswa melalui Model Kooperatif Tipe Make a Match Berbantuan Media Flash Card - Desi Rahmawati; E. Kus Eddy Sartono (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Learning Pancasila in class II with the lecture method will cause less active student involvement in the learning process. The right solution to overcome this problem is through improving student learning outcomes by implementing the Make A Match Type Cooperative learning model supported by Flash card media. The purpose of the classroom action research carried out is to provide an increase in student learning outcomes in the subject of Pancasila Education for Class II Students Through the Make A Match Type Cooperative Model Assisted by Flash card media at SD N Kandri Girisubo. This research was conducted in four stages, namely planning, action, observation and reflection. Obtaining student success data from student test results and observation sheets. Learning outcomes increased with an average gain of 62.5 in Cycle I to 75.4 in Cycle II learning, and the percentage of completeness increased from 66.8% to 78.6%. This increase proves that learning by implementing the Make a match type cooperative model with the help of flash card media in cycle II is very effective in providing increased activity and student learning outcomes in the aspects of knowledge, attitudes, and skills in the Pancasila Education subject. Thus, this research can be said to be successful, and the research cycle was stopped.